Literasi Teknologi dan Kematangan AIS sebagai Faktor Penentu Risiko Siber pada UMKM : Evaluasi Audit Berbasis Teknologi (Jurnal Kendali Akuntansi, 2025)
This study aims to analyze the influence of technological literacy, accounting information system maturity, and technology-based auditing on cyber risk in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The background of this research is based on the increasing adoption of digital technology by MSMEs, particularly in the management of financial information and business operations. However, this digital transformation has not been fully matched by system readiness or human resource competency, creating the potential for significant digital threats, including cyber risks that can impact business continuity. This study used a quantitative approach with a survey method involving 90 MSME respondents who have utilized digital accounting systems in their business activities. Data were collected through questionnaires and analyzed using multiple linear regression with the latest version of SPSS software. The results show that technological literacy and accounting information system maturity have a negative and significant effect on cyber risk. This means that the higher the level of technological literacy and the more mature the accounting information system implemented, the lower the level of cyber risk faced by MSMEs. On the other hand, technology-based audits did not show a significant impact on cyber risk, indicating that the effectiveness of audits using a technology approach is still suboptimal in the context of MSMEs. The coefficient of determination (R²) of 52.3% indicates that the variation in cyber risk can be explained by the three independent variables. This finding has practical implications for MSMEs and policymakers, namely the importance of strengthening technology and information systems capacity as a cyber risk mitigation strategy. Furthermore, there is a need to improve understanding and implement technology-based audits in a more structured manner to have a more significant impact on MSME digital security.